1998
DOI: 10.1159/000009993
|View full text |Cite
|
Sign up to set email alerts
|

Role of Serum Ceruloplasmin and Its Ferroxidase Activity on Preterm Labor

Abstract: The role of serum ceruloplasmin and its ferroxidase activity on preterm labor with or without rupture of the membranes was studied. Thirty-seven primigravid women between 31 and 35 weeks of gestation were investigated. Our material is divided into 3 groups. Group A consisted of 12 patients with premature rupture of the membranes; group B consisted of 10 patients with preterm labor but intact membranes, and group C consisted of 15 non-laboring patients. Patients with rupture of the membranes presented with stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
1
1
Order By: Relevance
“…23 Vitoratos et al have reported higher serum ceruloplasmin levels in patients with premature rupture of the membranes than in preterm delivery patients with intact membranes. 43 We did not find any statistical significance in maternal serum and amniotic fluid ceruloplasmin levels both in the preterm delivery and IUGR group. There is no study in the published work concerning the ceruloplasmin levels and risk of preterm delivery and IUGR.…”
Section: Discussioncontrasting
confidence: 61%
“…23 Vitoratos et al have reported higher serum ceruloplasmin levels in patients with premature rupture of the membranes than in preterm delivery patients with intact membranes. 43 We did not find any statistical significance in maternal serum and amniotic fluid ceruloplasmin levels both in the preterm delivery and IUGR group. There is no study in the published work concerning the ceruloplasmin levels and risk of preterm delivery and IUGR.…”
Section: Discussioncontrasting
confidence: 61%
“…Ogino M et al [12] showed that ceruloplasmin in cervicovaginal secretions was significantly higher in PROM cases (p<0.001) than non PROM cases and concluded that active ceruloplasmin in the cervicovaginal secretion might be a reliable clinical marker for term PROM. Vitoratos N, et al [13] have reported that the higher serum ceruloplasmin levels in patients with premature rupture of the membranes than those with preterm labor but intact membranes (p<0.05) as well as to non-labouring patients. They concluded that a loss of ferroxidase activity of ceruloplasmin in patients with rupture of the membranes and probably suggest a defect in the maternal defence mechanisms.…”
Section: Discussionmentioning
confidence: 97%